2012
DOI: 10.1073/pnas.1201734109
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia alters time perception by phase shifting the circadian clock

Abstract: Following general anesthesia, people are often confused about the time of day and experience sleep disruption and fatigue. It has been hypothesized that these symptoms may be caused by general anesthesia affecting the circadian clock. The circadian clock is fundamental to our well-being because it regulates almost all aspects of our daily biochemistry, physiology, and behavior. Here, we investigated the effects of the most common general anesthetic, isoflurane, on time perception and the circadian clock using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 36 publications
5
69
1
1
Order By: Relevance
“…In addition, the honey bee circadian system regulates complex physiological and behavioral processes such as sleep stages, spatiotemporal learning, sun-compass navigation, time perception, division of labor, mating and reproduction (von Frisch, 1967;Moore and Rankin, 1985;Goodwin and Lewis, 1987;Harano et al, 2007;Shemesh et al, 2007;Moore and Doherty, 2009;Johnson et al, 2010;Shemesh et al, 2010;Cheeseman et al, 2012;Eban-Rothschild and Bloch, 2012;GalindoCardona et al, 2012). Both the wide range of biological processes under circadian regulation and the extraordinary plasticity of the circadian network of these organisms potentially represent unique evolutionary challenges and solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the honey bee circadian system regulates complex physiological and behavioral processes such as sleep stages, spatiotemporal learning, sun-compass navigation, time perception, division of labor, mating and reproduction (von Frisch, 1967;Moore and Rankin, 1985;Goodwin and Lewis, 1987;Harano et al, 2007;Shemesh et al, 2007;Moore and Doherty, 2009;Johnson et al, 2010;Shemesh et al, 2010;Cheeseman et al, 2012;Eban-Rothschild and Bloch, 2012;GalindoCardona et al, 2012). Both the wide range of biological processes under circadian regulation and the extraordinary plasticity of the circadian network of these organisms potentially represent unique evolutionary challenges and solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Cheeseman et al (9) and Challet et al (10), isoflurane administration caused suppression of circadian gene expression but did not cause a shift in circadian pattern in investigated tissues. Cheeseman et al (9) kept animals in a DD cycle after anaesthesia administration, and they found a phase shift in circadian gene expression. The different effect of anaesthesia on circadian gene expression in our study may be due to light in the LD cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al (8) found that propofol administration significantly changes the expression of circadian genes in rat whole brain, and the influence of intravenous anaesthesia also persists for 24 hours after awakening from anaesthesia. Cheeseman et al (9) investigated the effect of the time of day of general anaesthesia administration and circadian gene expression profile in the brain of a honeybee (Apis mellifera). They found that this effect is dependent on the time of day of administration, and night-time anaesthesia did not shift the clock.…”
Section: Discussionmentioning
confidence: 99%
“…Cheeseman ve ark. (27) bal arılarında gündüz uygulanan izofluran anestezisinin per, cry ve CLOCK genlerini etkileyerek deneklerin zaman algılarında sapmaya neden olduğunu göstermişlerdir. SKÇ'teki GABA reseptörlerinin aktivasyonu ile CLOCK genlerin ekspresyonu baskılanabilir ve bu baskılanma anesteziklerin oluşturduğu sirkadiyan ritimdeki faz kayması oluşumu için bir mekanizma olabilir.…”
Section: Grupunclassified